2015
DOI: 10.15377/2409-9821.2015.02.01.1
|View full text |Cite
|
Sign up to set email alerts
|

CFD Benchmark Tests for Indoor Environmental Problems: Part 1 Isothermal/Non-Isothermal Flow in 2D and 3D Room Model

Abstract: Commercially available Computational Fluid Dynamics (CFD) software have been applied in indoor environmental design in recent years, but the prediction accuracy depends on an understanding of fluid dynamics fundamentals, in setting appropriate boundary and numerical conditions. This study aims to provide practical modelling information related to prediction accuracy and problematic areas in CFD applications in air conditioning and ventilation, through a series of benchmark tests and reported the results. Six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…51 Regarding the quality control of the CFD simulation, we carefully selected the scheme, algorithm and other numerical/boundary condition settings and followed the guidelines and benchmarks for the analysis of airflow fields in enclosed spaces. [52][53][54][55] The prediction accuracy of CFD analysis in the chamber was validated by using experimental result in terms of the convective mass transfer flux and confirmed to be reasonably consistent with the results of measurement via the naphthalene sublimation technique and simulation. 39 In this study, the calculation result of the airflow field as given in the previous report 39 was utilized for investigating the concentration distribution and identification of model parameters as described by equations (20) to (22).…”
Section: Outline Of the Cfd Analysissupporting
confidence: 65%
“…51 Regarding the quality control of the CFD simulation, we carefully selected the scheme, algorithm and other numerical/boundary condition settings and followed the guidelines and benchmarks for the analysis of airflow fields in enclosed spaces. [52][53][54][55] The prediction accuracy of CFD analysis in the chamber was validated by using experimental result in terms of the convective mass transfer flux and confirmed to be reasonably consistent with the results of measurement via the naphthalene sublimation technique and simulation. 39 In this study, the calculation result of the airflow field as given in the previous report 39 was utilized for investigating the concentration distribution and identification of model parameters as described by equations (20) to (22).…”
Section: Outline Of the Cfd Analysissupporting
confidence: 65%
“…Namely, at least 1/10 grids of building height are recommended for the RANS simulation of the outdoor flow field, as a guideline [22]. In addition, Ito et al [23] have shown that only two grids at the inlet position does not cause a large discrepancy in the indoor flow field distributions. The definitions of the openings are shown in Figure 1c, and the positions of the openings were chosen from three locations, denoted as 1, 2, and 3, in the vertical, and 1 and 2 in the spanwise directions.…”
Section: Methodsmentioning
confidence: 99%
“…The following performances were analyzed with environmental simulation techniques: (i) Optimization of the window opening position by solar radiation and indoor light environment analysis; (ii) Natural/cross-ventilation design supported by computational fluid dynamics (CFD) simulation [10][11][12] ; (iii) Optimization of opening position of horizontal slit-type windows using wind pressure coefficient analysis with CFD; and (iv) Annual heat load calculations to optimize the thermal insulation and natural/mechanical ventilation. Since the numerical simulation/analysis tools provide deterministic information for environmental conditions, the flexibility of design might decrease greatly when aiming at environmental optimization.…”
Section: Engineering Conceptmentioning
confidence: 99%